2018
DOI: 10.1080/00016357.2018.1437218
|View full text |Cite
|
Sign up to set email alerts
|

Oral shedding of HSV-1 and EBV and oral manifestations in paediatric chronic kidney disease patients and renal transplant recipients

Abstract: Therefore, it can be concluded that salivary shedding of HSV-1 and EBV in paediatric patients was more often found in renal transplant recipients than in the renal failure and control children. Transplanted recipients showed more oral manifestations than renal failure and control children did.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
35
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 34 publications
2
35
1
Order By: Relevance
“…Table summarizes the characteristics of the studies that evaluated dental caries among individuals with CKD compared to non‐CKD individuals. Twenty studies recruited participants with CKD from specialized centers (Almeida et al, ; Al‐Nowaiser et al, ; Andrade et al, ; Bayraktar et al, ; Caliento et al, ; Cengiz et al, ; Chamani et al, ; Davidovich, Schwarz, et al, ; Ertuğrul et al, ; Jaffe et al, ; Kanjanabuch et al, ; Limeres et al, ; Martins et al, ; Pakpour et al, ; Schmalz et al, ; Sobrado Marinho et al, ; Tadakamadla et al, ; Teratani et al, ; Tiwari et al, ; Wolff et al, ). One study sought participants in a textile industry (Garcez et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Table summarizes the characteristics of the studies that evaluated dental caries among individuals with CKD compared to non‐CKD individuals. Twenty studies recruited participants with CKD from specialized centers (Almeida et al, ; Al‐Nowaiser et al, ; Andrade et al, ; Bayraktar et al, ; Caliento et al, ; Cengiz et al, ; Chamani et al, ; Davidovich, Schwarz, et al, ; Ertuğrul et al, ; Jaffe et al, ; Kanjanabuch et al, ; Limeres et al, ; Martins et al, ; Pakpour et al, ; Schmalz et al, ; Sobrado Marinho et al, ; Tadakamadla et al, ; Teratani et al, ; Tiwari et al, ; Wolff et al, ). One study sought participants in a textile industry (Garcez et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies showed that individuals with CKD had significantly higher DMFT/DMFS scores than non‐CKD individuals ( p < 0.05) (Pakpour et al, ; Schmalz et al, ; Tiwari et al, ). Among the articles evaluating primary teeth, five studies showed that non‐CKD individuals had higher dmft/dmfs scores than those with CKD (Al‐Nowaiser et al, ; Andrade et al, ; Caliento et al, ; Ertuğrul et al, ; Jaffe et al, ). In three, statistically significant differences were found ( p < 0.05) (Al‐Nowaiser et al, ; Ertuğrul et al, ; Jaffe et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations